Asthma control in the quality of life levels of asthmatic patients' caregivers: a systematic review with meta‐analysis and meta‐regression - Daniela Duarte Costa; Paulo Márcio Pitrez; Nathália Foltz Barroso; Cristian Roncada (Brazilian Society of Pediatrics, 2019)
Objective: To perform a systematic review with meta‐analysis and meta‐regression to correlate the total scores of asthma control with the increase in the total scores of health‐related quality of life levels of parents of asthmatic children. Sources: The search was carried out in the following databases: PubMed (MEDLINE); Embase and ScienceDirect (Elsevier); SciELO and LILACs (Bireme) in June 2017. The included studies assessed asthma control through the Asthma Control Questionnaire (ACQ), Asthma Control Test (C‐ACT/ACT), and Global Initiative for Asthma (GINA) questionnaires, whereas the Pediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ) was applied to assess the HRQoL of parents and family members. Summary of the findings: 294 articles were evaluated in the selected databases, of which (n = 38) were excluded for duplicity; (n = 239) after the reading of the titles and abstracts and (n = 5) after reading the studies in full, totaling 12 studies eligible for the meta‐analysis. Of the 12 eligible articles, 11 (92%) were published in the last five years, and evaluated children and adolescents aged 1-20 years, totaling 2804 samples. In the evaluation of the correlation between the disease control scores by ACQ and C‐ACT/ACT, the results were satisfactory for both ACQ analyses [R2: −0.88; p < 0.001], and for C‐ACT/ACT [R2: 0.82; p < 0.001]. Conclusions: The results show that asthma control levels can influence the total HRQoL scores of parents or relatives of children and adolescents with asthma. Resumo: Objetivo: Realizar uma revisão sistemática, com meta-análise e meta-regressão para relacionar os escores totais do controle da asma com o aumento dos escores totais dos níveis de qualidade de vida relacionada à saúde de pais de crianças asmáticas. Fontes: As buscas foram aplicadas nas bases de dados: PubMed (Medline); Embase e ScienceDirect (Elsevier); SciELO e LILACs (Bireme). A busca foi realizada nas bases de dados em saúde em junho de 2017. Os estudos incluídos precisavam ter avaliados o controle da asma pelos questionários Asthma Control Questionnaire (ACQ), Asthma Control Test (C‐ACT/ACT) e Global Initiative for Asthma (GINA) e para a QVRS dos pais e familiares o Pediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ). Resumo dos achados: Foram avaliados 294 artigos nas bases de dados escolhidas, quanto aos níveis de duplicidade nas bases de dados (n = 38), excluídos por falta de enquadramento na leitura dos títulos e resumos (n = 239) e após leitura integral dos estudos (n = 05), restaram 12 estudos elegíveis à meta‐análise. Dos 12 artigos elegíveis, 11 (92%) foram publicados nos últimos cinco anos, avaliaram crianças e adolescentes de 1 a 20 anos, total de 2.804 amostras. Na avaliação da correlação entre a pontuação dos escores de controle da doença por ACQ e C‐ACT/ACT, os resultados se mostraram satisfatórios tanto para as análises de ACQ [R2: −0.88; p < 0,001], quanto para C‐ACT/ACT [R2: 0,82; p < 0,001]. Conclusões: Os resultados demonstram que os níveis de controle da asma podem influenciar nos escores totais da QVRS de pais ou familiares de crianças e adolescentes com asma. Keywords: Quality of life, Asthma, Disease control, Children, Caregivers, Parents, Palavras‐chave: Qualidade de vida, Asma, Controle da doença, Crianças, Cuidadores, Pais